Global trends and collaborative networks in gut microbiota-insulin resistance research: a comprehensive bibliometric analysis (2000–2024) - Abildinova, Gulshara Zh; Benberin, Valeriy V.; Vochshenkova, Tamara A.; Afshar, Alireza; Mussin, Nadiar M.; Kaliyev, Asset A.; Zhussupova, Zhanna; Tamadon, Amin (Frontiers in Medicine, 2024)
Background: The human gut microbiota plays a crucial role in maintaining metabolic health, with substantial evidence linking its composition to insulin resistance. This study aims to analyze the global scholarly contributions on the relationship between intestinal microbiota and insulin resistance from 2000 to 2024. Methods: A bibliometric analysis was conducted using data from Scopus and Web of Science Core Collection. The search strategy included terms related to "Gastrointestinal Microbiome" and "Insulin Resistance" in the title or abstract. Results: The analysis of 1,884 relevant studies from 510 sources was conducted, revealing a mean citation of 51.36 per manuscript and a remarkable annual growth rate of 22.08%. The findings highlight the significant role of gut microbiota in insulin resistance, corroborating prior studies that emphasize its influence on metabolic disorders. The literature review of the current study showed key mechanisms include the regulation of short-chain fatty acids (SCFAs) and gut hormones, which are critical for glucose metabolism and inflammation regulation. The analysis also identifies "Food & Function" as the most productive journal and Nieuwdorp M. as a leading author, underscoring the collaborative nature of this research area. Conclusions: The consistent increase in publications in the field of gut microbiota and insulin resistance indicates growing recognition of the gut microbiota's therapeutic potential in treating insulin resistance and related metabolic disorders. Future research should focus on standardizing methodologies and conducting large-scale clinical trials to fully realize these therapeutic possibilities.